Roman Pollak typograficznie. O współpracy z Janem Kuglinem w świetle korespondencji - Krzak-Weiss, Katarzyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The aim of the article is to analyse the relationship between Roman Pollak and Jan Kuglin, an accomplished typographer, through the lens of their surviving correspondence and the works they published together. The part of Pollak’s legacy that remains in the Archive of the Polish Academy of Science in Poznan is a modest one, consisting if four letters and four postcards, but extremely helpful in recreating the contacts between Pollak and Kuglin which lasted from the interwar period until professor Pollak’s death.